Carbon-Tailored Semimetal MoP as an Efficient Hydrogen Evolution Electrocatalyst in Both Alkaline and Acid Media - Li, Guowei; Sun, Yan; Rao, Jiancun; Wu, Jiquan; Kumar, Anil; Xu, Qiu Nan; Fu, Chenguang; Liu, Enke; Blake, Graeme R.; Werner, Peter; Shao, Baiqi; Liu, Kai; et al. (Advanced Energy Materials, 2018)
The electrolysis processes such as hydrogen evolution reaction (HER) require high efficient catalysts with robust surface stability. A high conductivity is also necessary to speed up the charge transport between the catalyst and the electrolyte. Recently, the observation of exceedingly high conductivity in the topological semimetal MoP, has provided a model catalyst to investigate the correlation between the electrical transport and the electrocatalytic activity for the HER. Thus, MoP is encapsulated in a Mo, P codoped carbon layer (MoP@C). This composite material exhibits outstanding HER performance, with an extremely low overpotential of 49 mV at a current density of 10 mA cm−2 and a Tafel slope of 54 mV dec−1 in an alkaline medium. In addition, electron transport analysis indicates that MoP exhibits high conductivity and mobility due to the existence of triple-point fermions and a complex Fermi surface. Furthermore, the presence of PC and MoC bonds at the interface between the carbon layer and the MoP particles modulates the band structure of MoP@C and facilitates fast electron transfer, accumulation, and subsequent delocalization, which are in turn responsible for the excellent HER activity.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electrocatalysts; hydrogen evolution reaction; MoP; topological semimetals